Kesalahan Penggunaan Preposisi di, ke, dan dari dalam Karangan Narasi Siswa Kelas VIII SMP Negeri 3 Rote Barat - Alfons, Junaerdi; Nitbani, Semuel H.; Pekuwali, Dian Sari A. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
ABSRACT This research aims to determine the understanding or errors in using the preposition in, to, and from in the narrative essays of class VIII students at SMP Negeri 3 Rote Barat. Data collection techniques use nontest and documentation techniques. The method used in the research is a descriptive qualitative method. The research results stated that, class VIII students at SMP Negeri 3 Rote Barat can be said to be able to use the prepositions in, to, and from narrative essays. This can be proven in the results of student achievement, nemely looking at the total number of 25 students, 22 students are said to be able to get a score of 75-100 with a percentage of 88%, while 3 students are said to be less able to get a score <75 with a percentage of 12%.